2021
DOI: 10.3390/ijms222413590
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Calcium ATPase-Neuroplastin Complexes Are Selectively Stabilized in GM1-Containing Lipid Rafts

Abstract: The recent identification of plasma membrane (Ca2+)-ATPase (PMCA)-Neuroplastin (Np) complexes has renewed attention on cell regulation of cytosolic calcium extrusion, which is of particular relevance in neurons. Here, we tested the hypothesis that PMCA-Neuroplastin complexes exist in specific ganglioside-containing rafts, which could affect calcium homeostasis. We analyzed the abundance of all four PMCA paralogs (PMCA1-4) and Neuroplastin isoforms (Np65 and Np55) in lipid rafts and bulk membrane fractions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…This result also confirms that the change in the basic level of intracellular Ca 2+ could be a result of partial raft domain disruption. However, this could be a result of various influences on raft domain-dependent calcium ion transporters, among them plasma membrane Ca 2+ ATP-ases [ 49 ] or a variety of Ca 2+ channels [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result also confirms that the change in the basic level of intracellular Ca 2+ could be a result of partial raft domain disruption. However, this could be a result of various influences on raft domain-dependent calcium ion transporters, among them plasma membrane Ca 2+ ATP-ases [ 49 ] or a variety of Ca 2+ channels [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GQ1b on neuronal membrane excitability has been well described and is related to membrane ion transport systems via the modulation of Ca 2+ channels by gangliosides [32]. Recent studies draw particular attention to the regulation of cellular ion homeostasis by gangliosides as one of the most prominent aspect of gangliosides actions [3,33]. Seemingly, gangliosides are implicated in membrane architectural and functional remodeling occurring in a human TLE pathology in much more complex ways than could have been perceived.…”
Section: Discussionmentioning
confidence: 99%
“…While the first PMCA was discovered a long time ago (Schatzmann, 1966), it was only recently found that the glycoproteins neuroplastin (NPTN) and basigin (BSG/CD147/EMMPRIN) can serve as subunits for PMCAs, and that they are essential for their plasma membrane localization and activity in a tissue-specific manner (Gong et al, 2018;Korthals et al, 2017;Schmidt et al, 2017). For example, in neurons the interaction of PMCA1 and PMCA2 with NPTNs NP55 and NP65 supports proper localization of these pumps into GM1 ganglioside-enriched lipid rafts (Ilic, Lin et al, 2021). NPTN controls PMCA expression in postsynaptic neurons, inner ear hair cells and T cells, and the NPTN-PMCA complex plays a crucial role in the regulation of synaptic plasticity, hearing and T cell activation Korthals et al, 2017;Lin et al, 2021;Malci et al, 2022).…”
Section: Pmca Structure In Complex With Neuroplastin and Basiginmentioning
confidence: 99%